Targeting deep-seated gold deposits: A study from the qujia gold deposit, Shandong province, China. (July 2021) - Wang, Qiang; Wang, Xueqiu; Liu, Hanliang; Tian, Mi; Zhang, Baoyun; Li, Ruihong; Yang, Deping; Xiong, Yuxin
Abstract: The Jiaodong gold (Au) province is the largest gold ore cluster in China and is an important world-class Au cluster area. Due to the exploitation of shallow Au deposits, prospecting for deep-seated Au deposits (>500 m) become increasingly important. This study uses the Qujia Au deposit to illustrate how to target deep-seated Au deposits by integrating soil and borehole geochemical data into a three-dimensional (3-D) geochemical model based on nine section lines with 652 surface soil samples and 823 rock samples from 30 boreholes. The additive log-ratio (alr)-factor analysis (FA) was adopted for soil geochemical data to identify element associations, and key element associations were extracted: F5 (Au–Ag association) indicates Au mineralization, and F3 (Hg–As–Br–I–Se association) represents the mineralizing agents. Combined with Au, Ag and Hg distribution by 3-D modelling based on borehole geochemical data, Hg is extremely competent as a vector for transportation channels of Au-bearing hydrothermal fluids in shallow space and ore-hosting space in deep space. Meanwhile, Au and Ag in primary halos not only form secondary halos near the primary halos but also remobilize, migrate, and deposit to form secondary anomalies at Lower-lying areas far away from primary halos due to their high mobility, while Hg is more stable and forms anomalies near the primary halos in supergene environments. Finally, two indicators for deep-seated Au ore bodies are constructed: one is the composite anomaly of Au, Ag, and Hg derived from soil geochemical data, and the other is the Hg anomaly derived from borehole geochemical data. Overall, this study successfully constructed indicators for deep-seated Au ore bodies by integrating soil and borehole geochemical data which is significant for geochemical exploration of deep-seated Au ore bodies in the same mineralization belt of the Jiaodong district. Highlights: 3D modelling is conducted by integrating soil and borehole geochemical data. Au and Ag are more mobile than Hg in supergene environments. Soil Au–Ag–Hg anomaly can effectively vector towards deep-seated concealed orebody. Borehole Hg anomaly can indicate transportation channels and concealed ore bodies.